Advances in organometallic chemistry. - Hill, Anthony F.; Fink, Mark J. (Academic Press, 2009)
Almost all branches of chemistry and material science now interface with organometallic chemistry--the study of compounds containing carbon-metal bonds. This widely acclaimed serial contains authoritative reviews that address all aspects of organometallic chemistry, a field that has expanded enormously since the publication of Volume 1 in 1964. * Fully updated and expanded to reflect recent advances * Illustrated with pertinenet examples from recent literature * Contributions from leading authorities and industry experts.